Does readiness to change influence pain-related outcomes after an educational intervention for people with chronic pain? A pragmatic, preliminary study. (4th May 2021) - Fletcher, Roland; Braithwaite, Felicity A; Woodhouse, Mellissa; MacInnes, Aaron; Stanton, Tasha R
ABSTRACT: Background : There is a strong association between chronic pain and unhelpful pain cognitions. Educating patients on pain neuroscience has been shown to reduce pain catastrophization, kinesiophobia, and self-perceived disability. This study investigated whether a group-based pain neuroscience education (PNE) session influenced pain-related outcomes, and whether readiness to change moderated these outcomes. Method : In a pragmatic pre-post-intervention study using a convenience sample, adults with chronic pain participated in one, 90–120 minute PNE session. Pain-related outcomes (i.e. pain catastrophization, kinesiophobia, disability, and pain neuroscience knowledge) and the Pain Stage of Change Questionnaire (PSOCQ) were assessed at baseline and immediately post-intervention. Paired t-tests evaluated pre-post changes in outcomes, and linear regression examined the impact of PSOCQ score changes on PNE-induced changes in clinical outcomes. Results : Sixty-five participants were recruited. All outcomes showed positive intervention effects ( p < .01). Relationships between changes in PSOCQ subscale scores and change in post-intervention pain-related outcomes were found; 'Pre-Contemplation' was positively associated with pain catastrophization ( p = .01), and 'Action' was negatively associated with kinesiophobia ( p = .03). Conclusion : Consistent with previous research, there were improvements in outcomes associated with chronic pain after PNE. Some of these improvements were predicted by changes in PSOCQ scores, however, these findings are preliminary and require further investigation using controlled research designs.